CUTTING EFFECTS ON ALFALFA (MEDICAGO SATIVA) GROWN UNDER UREA WITHOUT RHIZOBIUM MELILOTI FORAGE DYNAMICS - Ridouane, Ibrahim Barkire; Mouctari, Ousseini Mahaman M.; Touré, Ousseina Seydou; Mahamadou, Chaibou (International Journal of Research -GRANTHAALAYAH, 2024)
In order to see the effects of cutting on the forage dynamics of alfalfa to which urea was added instead of Rhizobium meliloti, this study was conducted in one year. A randomised full block design was used to conduct the trials. Four treatments were carried out with different doses of urea in experimental plots of 3 m by 1 m: a dose of 30g/plot; a dose of 40g/plot, a dose of 50g/plot and a last dose of 60g/plot. In addition to these treatments, there is the control which is alfalfa whose seeds have been inoculated. Forage production has fluctuated over the course of ten cuts done. The results are as follows : dose 1, the minimum obtained is 1597.71 kg DM/ha obtained in section 1 and the maximum is 2704 kg DM/ha obtained in section 5 ; dose 2, the minimum is 1943.97 kg DM/ha obtained in section 1 and the maximum is 3394.8 kg DM/ha in section 5 ; dose 3, the minimum obtained is 2424.00 kg DM/ha obtained in section 8 and the maximum is 4255.97 kg DM/ha in section 3; dose 4, the minimum is 2288.00 kg DM/ha in section 8 and the maximum is 4501.01 kg DM/ha in section 1. For the control, the minimum dry biomass obtained is 1549.00 kg DM/ha obtained in section 3 and the maximum is 2719.01 kg DM/ha obtained in section 3. In every cut, leaf/stem ratio was superior to 0.5. The results of this work show that cutting has a strong impact on alfalfa forage production. After this, alfalfa yield producted in this study is better than natural forage yield production, it means that alfalfa can be a solution for animal feed to face forage problems.